Role of Guanxi as perceived by chinese businessmen in Singapore. - Lee, Brenda Ai Ping. (2008)
This project has three objectives. Firstly, it studies the trend of the significance of guanxi in China as perceived by Singaporean businessmen. Secondly, it investigates the factors that cause the difference in the uses of guanxi in China and in Singapore. Finally, it studies why the guanxi in China differs from that in Singapore.